Hybrid Approaches to Fine-Grained Emotion Detection in Social Media Data - Schoene, Annika Marie (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
This paper states the challenges in fine-grained target-dependent Sentiment Analysis for social media data using recurrent neural networks. First, the problem statement is outlined and an overview of related work in the area is given. Then a summary of progress and results achieved to date and a research plan and future directions of this work are given.